(untitled) (Asean Journal of Engineering Education, 2023)
This study aims to investigate the effectiveness of active learning methodologies and technology tools in enhancing cognitive engagement among students in an online learning environment. Traditional teaching methods may not be sufficient to be replicated to engage students in online learning, which may lead to lower levels of cognitive engagement and reduced learning outcomes. Thus, it is essential to explore how technology tools and active learning strategy can be used to enhance cognitive engagement in online learning. This study involves the implementation of book-end method in active learning strategy and the adoption of technology tools such as Mentimeter, Padlet, Zoom or Microsoft Teams with breakout function and Canva in online classes. The theory of constructive alignment, how people learn (HPL) framework and scaffolding strategies are employed to ensure a seamless harmony between the provided activities and assessments. The students had to reflect their experience in this online learning classes and thematic analysis was conducted deductively using pre-determined themes based on cognitive engagement theory to analyse whether the students were cognitively engaged during the online lessons. The findings of this study indicate that book-end approach in active learning using higher order thinking skills activities and technology tools can significantly enhance cognitive engagement among students in online learning. The use of recaps infused with Mentimeter and breakout sessions powered by Zoom or MS Teams and Canva as the intermittent discussions tools, contribute to improved cognitive engagement. In conclusion, this study highlights the importance of using active learning methodologies and technology tools to enhance cognitive engagement in online learning. The findings suggest that educators should incorporate these tools and methodologies into their teaching practices to improve learning outcomes in online classes.